Numerical Study on the Risk of Infection in Adjacent Residential Spaces: Door Operation and the Impact of Outdoor Wind Speeds - Xunmei Wu; Mengtao Han; Hong Chen (Buildings)
Infectious diseases have profoundly impacted global health and daily life. To control virus transmission, countries worldwide have implemented various preventive measures. A critical pathway for infection spread is cross-infection within households, especially among family members in the same or adjacent rooms. This study uses numerical simulations to examine aerosol transmission characteristics in adjacent spaces in home settings and assess associated infection risks. The study evaluated the effects of factors such as outdoor wind speed, door gap leakage, and door opening actions on aerosol concentration and infection risk across various areas. Key conclusions include the following: Under prolonged lack of ventilation, aerosol leakage through the door gap is minimal, with the average aerosol concentration outside the bedroom remaining low (<0.04). In the absence of ventilation, aerosol accumulation primarily occurs within the bedroom. Under ventilated conditions, door gap leakage may increase infection risk in adjacent areas, suggesting a stay duration of no more than 75 min to keep infection risk below 30%. The findings provide practical recommendations for airtight design and activity area selection within residential spaces, offering valuable guidance for effective infection control measures.